2018
DOI: 10.1097/prs.0000000000004694
|View full text |Cite
|
Sign up to set email alerts
|

Lymph Flow Restoration after Tissue Replantation and Transfer: Importance of Lymph Axiality and Possibility of Lymph Flow Reconstruction without Lymph Node Transfer or Lymphatic Anastomosis

Abstract: Therapeutic, IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(47 citation statements)
references
References 35 publications
0
47
0
Order By: Relevance
“…Scaglioni et al reported the use of a combined pedicled superficial circumflex iliac artery perforator flap with LVA in defect reconstruction to prevent the development of lymphatic disorders and lymphorrea 18) . Yamamoto et al suggested tissue replantation or free flap transfer without lymph node or s-LVA to restore the lymph flow and reported success in 63% of the cases 19) . Guillier et al proposed in their article for lymphatic disorder the combination of pedicle flap with lympho-venous bypass as a lymphatic derivation concept that can improve the chronic morbidity scenarios of lymphatic complications 20) .…”
Section: Discussionmentioning
confidence: 99%
“…Scaglioni et al reported the use of a combined pedicled superficial circumflex iliac artery perforator flap with LVA in defect reconstruction to prevent the development of lymphatic disorders and lymphorrea 18) . Yamamoto et al suggested tissue replantation or free flap transfer without lymph node or s-LVA to restore the lymph flow and reported success in 63% of the cases 19) . Guillier et al proposed in their article for lymphatic disorder the combination of pedicle flap with lympho-venous bypass as a lymphatic derivation concept that can improve the chronic morbidity scenarios of lymphatic complications 20) .…”
Section: Discussionmentioning
confidence: 99%
“…6 11 18 26 27 28 30 34 35 Although all previous studies are on extremity lymphedema cases and no study reports on BL cases, similar findings can be expected in BL cases; early diagnosis of BL with ICG lymphography and appropriate interventions may improve prognosis of BL. 6 14 23 26 28 30 36 37…”
Section: Discussionmentioning
confidence: 99%
“…Lymphedema is a chronic condition of lymphatic impairment commonly caused by infection, surgery, or radiation therapy [1][2][3][4]. Inflammation caused by local immune insufficiency and abnormal lipid profiles also result in lymphatic impairment [5][6][7][8][9]. Disrupted lymphatic flow leads to fluid accumulation in the regional interstitium that could result in cellular proliferation, fibrosis, adipose 상지에서의 혈관성 림프절 전이술의 미용적 삽입을 위한 새로운 수용부: 초기 결과 tissue hypertrophy, and skin breakdown [2,10].…”
Section: Introductionmentioning
confidence: 99%
“…Disrupted lymphatic flow leads to fluid accumulation in the regional interstitium that could result in cellular proliferation, fibrosis, adipose 상지에서의 혈관성 림프절 전이술의 미용적 삽입을 위한 새로운 수용부: 초기 결과 tissue hypertrophy, and skin breakdown [2,10]. Owing to the chronic edematous conditions and inflammation, the postoperative rehabilitation and quality of life of lymphedema patients, approximately > 250 million worldwide, are affected [2,5]. Despite the high incidence of lymphedema, it remains a challenge for reconstructive surgeons due to the lack of curative treatment options [1].…”
Section: Introductionmentioning
confidence: 99%